Willingness to pay for organic products in Texcoco, State of Mexico - Hernandez Ortiz, Juan; Trujillo Murillo, Juan; Martinez Damian, Miguel Angel (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of the study was to estimate the willingness to pay (DAP) for organic products in Texcoco, State of Mexico, as well as determine the socioeconomic variables that most influence the DAP of people for organic products, under the hypothesis that there is a DAP positive among the participants. 130 surveys were applied in the municipality of Texcoco, State of Mexico in the period from January 1 to March 31, 2017. The DAP was estimated for organic products in the area, using the contingent valuation method and a Logit Binomial model, using the Nlogit software, the variables that explain the DAP are price, gender, age, marital status, level of education and income, concluding that the inhabitants of the study area are willing to pay an extra amount in the price of basic products (lettuce, tomato and rice) if they are produced organically. In the case of lettuce, a DAP of 7.50 $ piece was determined, for tomato 11.00 $ kg and for rice 32.5 $ kg, which represents 53%, 41.5% and 2228% respectively.
Keywords: contingent valuation; DAP; logit-binomial model